Evaluasi nilai difusivitas ion kalsium dan magnesium pada proses low salinity waterflood di batuan Berea - Yusardhany Yusuf; Suryo Purwono; Sang Kompiang Wirawan (Jurnal Rekayasa Proses, 2017)
In recent years Low Salinity Waterflood (LSW) had been supposed as trusty method to improve oil recovery and the most essential aspect is a alteration of divalent ion concentration in reservoir pore volume as a respon LSW. The objective of this paper are to find divalent diffusivity constant (Ca2+ and Mg2+) in berea sandstone by ionsmass conservation equation along with Atomic Absorption Spectroscopy (AAS) as validation. The study was conducted at 2 berea core having porosity : 0.235 and 0.230 and permeability : 661 mD and 550 mD, we use synthetic formation water accordance to